PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LARUTAN PENYANGGA DI KELAS XI IPA SMAN 10 PEKANBARU - Elsy Indria; Roza Linda; R. H.Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research about application of the active learning strategy type learning tournament was conducted to improve students’ achievement on the buffer solution in class XI IPA SMAN 10 Pekanbaru. This research was experimental research based on pretest-posttest design. The samples of this research were the students of class Xl IPA 3 as a control class and students of class XI IPA 2 an experimental class that selected randomly after homogeneity test. Experimental class was applied the active learning strategy type learning tournament, while the control class was not applied. Data analysis technique used the t-test. Based on result of the analysis data obtained tarithmetic> ttable is 3,13 > 1,67, means that the application of active learning strategy type learning tournament could improve students’ achievement on the subject of buffer solution in class XI IPA SMAN 10 Pekanbaru with an increasing percentage of 12,6%.Key Words : Active Learning Strategy Type Learning Tournament, Learning Achievement, and Buffer Solution